The Moderating Role of Resilience: When Abusive Supervision Impacts Distributive Justice and Employees’ Voice - Khan, Rizwan (International Journal of Contemporary Economics and Administrative Sciences, 2019)
The purpose of this study is to investigate the role played by abusive supervision in decreasing the voice of employees. This study tested the mediating role of distributive justice in the relationship between abusive supervision and employee’s voice and moderating role of resilience in the relationship between abusive supervision and employee voice, and abusive supervision and distributive justice as well. A sample of 461 employees was contacted from 3S and 2S dealerships of automobiles sector of Pakistan. Using convenience sampling technique, data was collected through four structured questionnaires. Respondents duly filled in consent form for being participants of the study. To avoid variable biasedness Time Lag Technique was used for collecting data. Data Analyses were carried out by using SPSS and AMOS. Abusive supervision was found having negative impact on employees’ voice. Perception of abusive supervision has a negative impact on perception of distributive justice which in turn decreases employees’ voice. Resilience as a psychological resource has been found moderating the relationship between abusive supervision and employees’ perception of distributive justice, and the relationship between abusive supervision and employees’ voice. This study provides an insight to managers to figure out the adverse impact of abusive supervision on voice behaviors of employees. Abusive supervision works as a hurdle in voicing the silence of the subordinates. Mangers, therefore, need to take measures for discouraging abusive supervision in the work place. An abuse free organizational environment will induce employees to give their much-needed feedback and opinion in the organizational matters. Moreover, managers need to find ways to develop resilience in the employees as resilience like other components of PsyCap is a state which can be developed and strengthened. The present study investigates the supervisor’s abusive behavior to be an obstacle in voicing the silence of subordinates. It provides evidence that distributive justice mediates the relationship between abusive supervision and employees voice behaviors. This study broadens the understanding that how abusive supervision leads to employees’ voice behaviors through mediation of distributive justice, moreover, the mitigating role of resilience, (a component of Psychological Capital), has been emphasized in this study.